Tính toán quỹ đạo thiết bị bay không người lái - Từ, Phan Văn (Journal of Computer Science and Cybernetics, 2016)
The calculating trajectory of nonpilot fly equipment is complex problem but very important. Before, this problem was solved approximately by programming method: Euler, Adams, Runge-Kutta… Now there are new tools for the  finding solution of this problem. I attempt to solve this problem by simulink method. These results will give us the conclusion about practical meaning if this problem.